Synthesis and characterization of new 4-aryl-2-(2-oxopropoxy)-6-(2,5-dichlorothiophene)nicotinonitrile and their furo[2,3-b]pyridine derivatives: Assessment of antioxidant and biological activity - Al‐Refai, Mahmoud; Ibrahim, Mohammad; Al‐Fawwaz, Abdullah; Geyer, Armin (European Journal of Chemistry, 2018)
A new series of furo[2,3-b]pyridine derivatives bearing aryl substituents were synthesized in two steps, where, the cyano-(2H)-pyridones (1a-l) were converted to the corresponding nicotinonitriles (2a-l), followed by the Thorpe-Ziegler ring cyclization to the furo[2,3-b]pyridine derivatives (3a-l). All new compounds were characterized by 1D-NMR experiments (1H and 13C) and 2D-NMR experiments (COSY, HMBC and HSQC), as well as ESI-MS and HR-ESI-MS data. The new compounds were screened for their antioxidant activities by 2,2-diphenyl-1-picryl-hydrazylhydrate (DPPH) free radical assay. The highest radical scavenging effect was observed for nicotinonitriles 2d, 2h and 2l and furo[2,3-b]pyridines 3b, 3f and 3j by methanolic solvent at 4.0 mg/mL concentration. Remarkably, all nicotinonitriles and furo[2,3-b]pyridine exhibited a significant radical scavenging activity after 24 and 48 hours compared with 0.5 hour.